Adherence to COVID-19 nutritional guidelines and their impact on the clinical outcomes of hospitalized COVID-19 patients. (December 2021) - Ho, Dang Khanh Ngan; Nguyen, Hung Song; Irnandi, Dicky Faizal; Faradina, Amelia; Dang, Tri Do; Wiratama, Bayu Satria; Nurwanti, Esti; Hadi, Hamam; Chuang, Yung-Kun; Tinkov, Alexey A.; Skalny, Anatoly V.; Chang, Jung-Su
Summary: Background & aims: Coronavirus disease 2019 (COVID-19) patients are at high risk of malnutrition, and their doctors are part of a multidisciplinary team, including nutritionists. However, adherence to nutritional guidelines may be difficult in the context of capacity constraints during the COVID-19 pandemic. The aim of this study was to investigate barriers to doctors' adherence to nutritional guidelines and the impacts of guideline adherence on the outcomes of hospitalized COVID-19 patients. Methods: A multinational electronic survey involving 51 doctors was conducted between November 2020 and January 2021 from 17 COVID-19-designated hospitals in countries with high (Indonesia) and low (Vietnam) numbers of confirmed COVID-19 cases. Results: In general, doctors reported concerns related to nutritional practices in patients with Covid-19 which included feeling stress when performing medical nutritional therapy (65%), lacking self-efficacy or confidence in performing nutritional care (49%), lacking clear nutritional guidelines (45%), and experiencing budget limitations (33%). A regression analysis adjusted for age, country, and the number of hospitalized COVID-19 cases revealed that guideline knowledge (β: −1.01 (−1.78,  −0.23); p = 0.012) and awareness of guidelines (β: −1.37 (−2.66,  −0.09); p = 0.037) were negatively correlated with the length of stay of critically ill COVID-19 patients, but non-significant after adjusting for specialization of the doctor. When stratified according to country, a significant relationship between guideline adherence and length of stay of critically ill patients was only found in Vietnam [guideline adherence: β: −0.55 (−1.08,  −0.03); p = 0.038; guideline knowledge: β: −1.01 (−1.9,  −0.13); p = 0.027] after adjusting for age, specialty, and number of hospitalized COVID-19 cases. In Indonesia, the significant relationship between guideline adherence and mortality of COVID-19 patients remained strong (β: −14 (−27,  −1); p = 0.033) after adjusting for age, specialty, and number of hospitalized COVID-19 cases Conclusions: Inadequate nutritional knowledge is a key barrier to guideline adherence, and this was international and may be related to doctors' specialties and the COVID-19 pandemic. Adherence to nutritional guidelines may represent a prognostic factor for survival in COVID-19 patients.